The Effects of oil prices on the spot exchange rate (MXN/USD) a VAR analysis for Mexico from 1991 to 2017 - Sergio García; Eduardo Saucedo; Alejandro Velasco (Universidad Autónoma Metropolitana Unidad Azcapotzalco, 2018)
The Mexican economy has been historically dependent on oil. For this reason, our research investigates whether oil prices influence the Mexican peso exchange rate against the U.S. dollar. The database is made up of quarterly reports, taken from 1991 to 2017. A Vector Autoregressive Model (VAR) was implemented, which included spot and future oil prices, money supply, and GDP growth rates for Mexico and the United States, and the nominal MXN/USD exchange rate. Results indicate that an increase/decrease in the oil spot price appreciates/ depreciates the Mexican peso against the U.S. dollar. Results also indicate, however, that future oil prices do not have a statistically significant effect on the exchange rate. Further, the study found that in order to keep the Mexican peso to U.S. dollar exchange rate stable, the money supply and GDP growth rate in Mexico should be similar to those same variables in the United States. Lastly, the impulse response functions show that such effects disappear in the months following unexpected price shocks.